Irenaeus on Natural Knowledge - Briggman, Anthony (Church history and religious culture, 2015)
Over a century of research has produced little agreement on the question of whether Irenaeus of Lyons recognized a natural knowledge of God. This article raises the question anew by considering the interpretive issues surrounding the passage at the center of the debate, Against Heresies 2.6.1. It challenges past readings and offers one of its own. I contend that an affirmation of natural knowledge plays the leading role in the argument of AH 2.6.1. This being the case, this text does not undermine references to natural knowledge that appear elsewhere in Irenaeus’s corpus, as Th.-André Audet would have us believe, but supports them. Irenaeus, then, does indeed recognize a natural knowledge of God, the product of discursive reasoning about the creation and providence of God.